Low Proportion of Recent Human Immunodeficiency Virus (HIV) Infections among Newly Diagnosed Cases of HIV Infection as Shown by the Presence of HIV-Specific Antibodies of Low Avidity - Puchhammer-Stöckl, Elisabeth (American Society for Microbiology, 2005)
The time between human immunodeficiency virus (HIV) infection and diagnosis is mostly unknown. Two hundred five newly diagnosed patients were investigated for the duration of their HIV infection by avidity testing. Recent HIV infection was identified in 27.3% of the cases. Early diagnosis was achieved significantly less frequently in heterosexually infected persons than in other patients.